Effectiveness of Brazilian and German teams and the teams defeated by them during the 17th FIFA World Cup - Szwarc, A. (Kinesiology, 2004)
An attempt was made to indicate the factors of an effective soccer game. In order to do this technical and tactical actions were compared in a game of Brazilian and German players, the finalists of the 2002 World Cup, and players of the teams which lost to them. Twelve games recorded on audiovisual tapes were used for comparative purposes. The game data were registered on observation spreadsheets. Szwarc's method of game description and notation was applied. It was proved that shots at goal during the games, good passing and taking the ball away from an opponent in one-on-one situations are the factors which make the difference between the successful and unsuccessful teams.